Upaya Pencegahan dan Penanganan dalam Kasus Kekerasan Terhadap Perempuan dan Anak - Simanjuntak, Awan Catharina Letare; Situmorang, Cindy; Situmorang, Felix Kevin; Sitinjak, Fransiska; Ulwan, Gina Nuzul; Saragih, Gloria Luisa; Marbun, Rany; Siregar, Waliyul Maulana (Media Hukum Indonesia (MHI), 2024)
Violence is any form of action that causes physical, sexual or psychological suffering to women or children. Violence against women includes harassment, domestic violence, rape, torture, insults and others. Violence against children includes physical violence, psychological violence, and exploitation. Prevention efforts include participating in training from the health system and health workers. The author uses a literature study methodology or library study and uses data analysis techniques. The purpose of this study is to gain a better understanding of the various ways that can be done to prevent and handle cases of violence against children and women.